Jean Baudrillard / Selected Writings - Baudrillard Jean; Poster Mark (Policy Press, 1988)
Acknowledgements, Notes on the Translation, Introduction, The System of Objects, Consumer Society, For a Critique of the Political Economy of the Sign, The Mirror of Production, Symbolic Exchange and Death, On Seduction, Simulacra and Simulations, Fatal Strategies, The Masses: The Implosion of the Social in the Media, Index.